(untitled) (London Journal of Medical and Health Research, 2023)
Systemic Lupus Erythematosus (SLE) is an autoimmune multi systemic disease which affects many organs which can lead to mortality. A 33-year-old female came with diminution of vision in both eyes for 5 days. Her best corrected visual acuity is 6/12 and 6/60 in right and left eye respectively. Fundus examination showed blurred and elevated disc margin with dilated veins. Macular OCT showed increased macular thickness. MRI brain and orbit were normal. The patient was admitted to hospital for further investigation and treatment. Injection Mannitol 20% 200ml was infused and Tab Acetazolamide was given. The patient complained of severe abdominal pain for which she was referred to physician. On the physical and blood examination she was found to a case of SLE.